PERLINDUNGAN HUKUM BAGI INVESTOR RITEL TERHADAP PRAKTIK INSIDER TRADING DI PASAR MODAL - Moh Rafi Maulana; Achmad Hariri (Universitas Labuhanbatu, 2026)
Legal protection for retail investors in Indonesia’s capital market has become a critical issue, particularly in relation to insider trading practices that undermine market fairness and transparency. Insider trading creates information asymmetry, allowing certain parties to exploit material non-public information to gain unfair advantages, thereby disadvantaging retail investors and threatening market integrity. This study aims to analyze the legal protection framework for retail investors against insider trading within Indonesia’s capital market regulations. The research employs a normative juridical method with a statutory approach, supported by library research, focusing on Law No. 8 of 1995 on Capital Markets and Law No. 4 of 2023 on Financial Sector Development and Strengthening. The findings indicate that insider trading prohibitions are explicitly regulated under Articles 95, 96, 97, and 98 of the Capital Market Law, which aim to uphold principles of disclosure and fairness in securities transactions. However, the effectiveness of legal protection for retail investors remains limited due to challenges in law enforcement, supervision, and evidentiary processes. This study highlights the need to strengthen enforcement mechanisms, enhance transparency, and optimize the role of regulatory authorities in ensuring a fair and accountable capital market. From a theoretical perspective, this research contributes to the discourse on investor protection by emphasizing the role of information asymmetry in shaping regulatory responses to insider trading.Keywords: Capital Market, Insider Trading, Retail Investors, Legal Protection, Information Asymmetry